Pengaruh Social Media Marketing, Orientasi Kewirausahaan Dan Label Halal Produk Terhadap Keunggulan Bersaing Umkm Sektor Kuliner Di Jombang - Apriliyana, Yeni; Nurafini, Fira (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study investigates the influence of social media marketing, entrepreneurial orientation, and halal product labeling on the competitive advantage of culinary Micro, Small, and Medium Enterprises (MSMEs) in Jombang Regency, Indonesia. Employing a quantitative research design with a purposive sampling technique, this study involved 105 culinary MSMEs that have obtained halal certification and actively utilize social media platforms for marketing purposes. Primary data were collected through an online questionnaire distributed via Google Forms and processed using SPSS software. The findings reveal that social media marketing, entrepreneurial orientation, and halal product labeling each exert a positive and significant effect, both partially and simultaneously, on the competitive advantage of culinary MSMEs in Jombang. These results underscore the importance of optimizing digital marketing strategies, fostering a strong entrepreneurial mindset, and adhering to halal certification standards as integrated efforts to enhance the sustainable competitive edge of culinary MSMEs.